REAKSI INVESTOR DI BURSA EFEK INDONESIA TERHADAP PENGUMUMAN PENURUNAN BBM - Maria J. Esomar (Soso-Q : Jurnal Manajemen, 2018)
In the business world, economic events can affect the price and volume of trading in the stock market. The capital market is now more sensitive to the economic changes that occur, including the announcement of increases or decreases in fuel oil. The purpose of this study was to determine the reaction of the capital market to the announcement of fuel reduction. This study uses the event study method where the event study is a study that studies the market reaction to an event (event) whose information is published as an announcement. In this study the calculation of abnormal returns uses the Single Index Model (Market Model).This study uses an event study approach, with samples of energy and mining-based companies listed on LQ 45. The results of this study indicate that the capital market reacts to the announcement of the reduction in fuel prices. Based on this research, the announcement of the third reduction in BBM has significant information content around the announcement area or after the event date ... but it does not have high information content around the area before the announcement.Keywords: Announcement of Fuel Reduction, Abnormal Return, Study Event.